Pengaruh Kepemimpinan, Prosedur Kerja, Reward, Punishment, Lingkungan dan Pelatihan terhadap Prestasi Kerja Pegawai Badan Pendapatan Daerah Kabupaten Muara Enim - Balkis, Balkis; Hamid, Abdul; Fitriya, Fitriya (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The author conducted the research to know and analyze the influence of leadership, work procedures, rewards, punishment, environment, and training individually and collectively on the work performance of Muara Enim Regency Regional Revenue Agency employees. The research method used in this study is quantitative, using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, and normality test. The descriptive and inferential analysis used statistical calculations with multiple regression formulas, partial test simultaneous test, and the coefficient of determination. The research results showed that leadership significantly affected the work performance of Muara Enim Regency Regional Revenue Agency employees. Work Procedures significantly affect the work performance of Muara Enim Regency Regional Revenue Agency employees. Rewards significantly affect the work performance of employees of the Muara Enim Regency Regional Revenue Agency. Punishment significantly affects the work performance of employees of the Regional Revenue Agency of Muara Enim Regency. The environment significantly affects the work performance of employees of the Muara Enim District Revenue Agency. Training significantly affects the work performance of employees of the Regional Revenue Agency of Muara Enim Regency. Leadership, work procedures, rewards, punishment, environment, and training significantly affect the work performance of Muara Enim Regency Regional Revenue Agency employees.